PARP Inhibitor Olaparib Use in a BRCA1-Positive Patient With Metastatic Triple-Negative Breast Cancer, Without the Initial Use of Platinum-Based Chemotherapy, Showing Significant Rapid Near Resolution of Large Liver Metastasis While Patient Experienced Gout-Like Symptoms. (August 2019) - Matthews Hew, Trevanne; Zuberi, Lara
Triple-negative breast cancer (TNBC) accounts for 20% of breast cancers diagnosed worldwide. This subtype of breast cancer tends to behave more aggressively, and unlike other breast cancer subtypes, there are no standard targeted treatments for most patients. However, up to 20% of patients with TNBC harbor a breast cancer gene (BRCA) mutation, particularly in BRCA1 . For patients who carry this gene mutation, this opens the door for new management options by the use of newer agents such as polyadenosine diphosphate-ribose polymerase (PARP) inhibitors in the metastatic setting. Given that this is uncommon and that PARP inhibitors have only recently received Federal Drug Administration approval, the experience with these drugs is relatively new. In this article, we present a case of a patient treated in this setting with olaparib who developed an unanticipated side effect as a result of the high efficacy of the drug.